Hubungan Pengetahuan Dan Sikap Ibu Hamil Tentang Gizi Seimbang Dengan Pencegahan KEK (Kekurangan Energi Kronis) Pada Ibu Hamil Diwilayah Kerja Puskesmas UPTD Bandar Kecamatan Bandar Kabupaten Bener Meriah - Hartini, Desi; HS, Nurlaely; Hudnah, Hudnah (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Chronic Energy Deficiency (CED) is one of the problems faced by pregnant women, the indirect cause of CED is an imbalance in nutritional intake (energy and protein). The impact of CED is anemia, prematurity, low birth weight (LBW), and stunting. WHO data from 2024 shows that CED in pregnant women is (75%) of the maternal mortality rate. In Indonesia, as many as 1.35 million pregnant women experience CED, while in Bener Meriah Regency in 2024, out of 3,431 pregnant women, 193 were found to have CED, and in the study area, 59 pregnant women experienced CED. This condition indicates that the problem of CED is still quite high, so early prevention efforts are needed. The purpose of this study was to analyze the relationship between knowledge and attitudes of pregnant women about balanced nutrition and CED prevention in the Bandar Community Health Center work area. This type of research is quantitative with a cross-sectional design. The sampling technique used a total sampling technique with 72 respondents. The instrument used was a questionnaire. Data analysis was carried out univariately and bivariately with the chi-square test. The chi-square test results showed a significant relationship between knowledge and CED prevention (p-value = 0.002), and a significant relationship between attitude and CED prevention (p-value = 0.021). Pregnant women are advised to adopt a balanced nutritional diet, consume affordable nutritious food according to their family's economic situation, and maintain a positive attitude to prevent CED in pregnant women.